Detection of Genetic Polymorphism in Iraqi Barley using SSR-PCR Analysis - Al-Hadeithi , Zeina S. M. (Iraqi Journal of Science, 2022)
Nine Iraqi varieties of barley (Hordeum vulgare L.) has been differentiated and diagnosed using simple sequence repeat markers to detect their genetic polymorphism. Six SSR primers were used for genetic screening of barley samples (IPA 265, IPA 99, Tuwaitha, Hitra, Rayhan, Shuaa, Bawadi, Samir and Al_khair). These primers generated total PCR product (11) bands divided to 8 polymorphic bands 3 monomorphic bands. the percentage of polymorphism 80% ranged between (50-100%). a mean value of polymorphic band per primer was 1.6 . these primers produced amplification fragment at Molecular weight between 75-900 bp. One unique band was generated at size 200bp, this band can be used as a DNA profiling of all studied genotypes. These results appeared genetic distances ranged between (0.01098-0.99708) among studied varieties. Using the unweighed pair-group method using arithmetic averages (UPGMA) cluster analysis, nine barley landraces were clustered into two main clusters depending on their ancestors and to their spike type (two-row and six-row barley). These results will be useful for barley germplasm management in terms of biodiversity protection and breeder’s rights protection.